The predictive state: science, territory and the future of the Indian climate - Mahony, Martin (SAGE Publications, 2014)
Acts of scientific calculation have long been considered central to the formation of the modern nation-state, yet the transnational spaces of knowledge generation and political action associated with climate change seem to challenge territorial modes of political order. This paper explores the changing geographies of climate prediction through a study of the ways in which climate change is rendered knowable at the national scale in India. The recent controversy surrounding an erroneous prediction of melting Himalayan glaciers by the Intergovernmental Panel on Climate Change (IPCC) provides a window onto the complex and at times antagonistic relationship between the Panel and Indian political and scientific communities. The Indian reaction to the error, made public in 2009, drew upon a national history of contestation around climate change science, and corresponded with the establishment of a scientific assessment network (INCCA) which has given the state a new platform on which to bring together knowledge about the future climate. I argue that INCCA is indicative of the growing use of regional climate models within longer traditions of national territorial knowledge-making, allowing a re-scaling of climate change according to local norms and practices of linking scientific knowledge to political action. I illustrate the complex co-production of the epistemic and the normative in climate politics, but also seek to show how co-productionist understandings of science and politics can function as strategic resources in the ongoing negotiation of social order. In this case, scientific rationalities and modes of environmental governance contribute to the contested epistemic construction of territory and the evolving spatiality of the modern nation-state under a changing climate.